In situ study of the thermal stability of supported Pt nanoparticles and their stabilization via atomic layer deposition overcoating. Issue 21 (22nd May 2020) - Solano, Eduardo; Dendooven, Jolien; Feng, Ji-Yu; Brüner, Philipp; Minjauw, Matthias M.; Ramachandran, Ranjith K.; Van Daele, Michiel; Van de Kerckhove, Kevin; Dobbelaere, Thomas; Coati, Alessandro; Hermida-Merino, Daniel; Detavernier, Christophe
Abstract : Supported Pt nanoparticle stabilization via Atomic Layer Deposition overcoating with Al2 O3 has been proved to prevent particle coarsening during thermal annealing for widely spaced nanoparticles while ensuring surface accessibility for applications. Abstract : Downscaling of supported Pt structures to the nanoscale is motivated by the augmentation of the catalytic activity and selectivity, which depend on the particle size, shape and coverage. Harsh thermal and chemical conditions generally required for catalytic applications entail an undesirable particle coarsening, and consequently limit the catalyst lifetime. Herein we report an in situ synchrotron study on the stability of supported Pt nanoparticles and their stabilization using atomic layer deposition (ALD) as the stabilizing methodology against particle coarsening. Pt nanoparticles were thermally annealed up to 850 °C in an oxidizing environment while recording in situ synchrotron grazing incidence small angle X-ray scattering (GISAXS) 2D patterns, thereby obtaining continuous information about the particle radius evolution. Al2 O3 overcoat as a protective capping layer against coarsening via ALD was investigated. In situ data proved that only 1 cycle of Al2 O3 ALD caused an augmentation of the onset temperature for particle coarsening. Moreover, the results showed a dependence of the required overcoat thickness on the initial particle size and distribution, being more efficient ( i.e. requiring lower thicknesses) when isolated particles are present on the sample surface. The Pt surface accessibility, which is decisive in catalytic applications, was analyzed using the low energy ion scattering (LEIS) technique, revealing a larger Pt surface accessibility for a sample with Al2 O3 overcoat than for a sample without a protective layer after a long-term isothermal annealing.